Hubungan Kemampuan Literasi Digital Dengan Hasil Belajar Siswa di SMK Negeri 1 Painan - Alfadila, Wahyu; Alfiriani, Adlia; Irsyadunas, Irsyadunas (Universitas Labuhanbatu, 2025)
The rapid development of digital technology encourages the importance of developing digital literacy in students. This study aims to reveal the relationship between digital literacy and student learning outcomes at SMK Negeri 1 Painan. Quantitative research methods with simple random sampling techniques were used in this study. Data analysis was carried out using normality, homogeneity, linearity, and Pearson correlation tests. The results of the study showed a positive relationship between digital literacy and student learning outcomes, although the correlation found was relatively weak (r = 0.372, p < 0.05). This finding indicates that increasing digital literacy can contribute to improving student learning outcomes. However, further research is needed with more specific variables to reveal the influence of digital literacy in more depth. The results of this study provide important implications for the development of curriculum and learning that integrates digital literacy to improve the quality of education.